"(Diphosphine)Nickel"‐Catalyzed Negishi Cross‐Coupling: An Experimental and Theoretical Study. Issue 21 (2nd April 2015) - Nicolas, Emmanuel; Ohleier, Alexia; D'Accriscio, Florian; Pécharman, Anne‐Frédérique; Demange, Matthieu; Ribagnac, Philippe; Ballester, Jorge; Gosmini, Corinne; Mézailles, Nicolas
Abstract The use of a strongly donating "(bis‐dialkylphosphine)Ni" fragment promotes the catalytic coupling of a large range of ArCl and ArZnCl derivatives under mild conditions. Stoichiometric mechanistic investigations and DFT calculations prove that a Ni0/NiII cycle is operative in this system.